2009
DOI: 10.1002/adem.200900130
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Transfer Coefficient for Cellular Materials Modelled as an Array of Elliptic Rods

Abstract: Convective heat‐transfer coefficients in foam‐like materials, modelled as an array of elliptic rods, are numerically determined. An incompressible fluid is considered, flowing through an infinite foam‐like material with an arbitrary solid temperature. A repetitive cell is identified and periodic boundary conditions are applied. Turbulence is handled with both low and high Reynolds number formulations. The interfacial heat‐transfer coefficient is obtained by volume integrating the distributed variables obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Kuwahara et al [49] conducted exhaustive numerical experiments with in-line arrangement of square rods in order to determine the convective heat-transfer coefficient. Moreover, a numerical determination was performed by de Lemos and Saito [50] in cellular materials, in which the solid matrix is treated as an ordered array of elliptic rods. In the present study, however, the unit cell geometry shown in Fig.…”
Section: Application To Stratified Porous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Kuwahara et al [49] conducted exhaustive numerical experiments with in-line arrangement of square rods in order to determine the convective heat-transfer coefficient. Moreover, a numerical determination was performed by de Lemos and Saito [50] in cellular materials, in which the solid matrix is treated as an ordered array of elliptic rods. In the present study, however, the unit cell geometry shown in Fig.…”
Section: Application To Stratified Porous Mediamentioning
confidence: 99%
“…A detailed description of the evaluation of this unknown integral is given by Quintard et al [50]. n mf Á k m rb mf ¼ n mf Á k f rb ff þ n mf k f at A fm…”
Section: Appendix B Closure Problemsmentioning
confidence: 99%